Comparative Safety and Effectiveness of Ticagrelor versus Clopidogrel in Patients With Acute Coronary Syndrome: An On-Treatment Analysis From a Multicenter Registry - Almendro-Delia, Manuel; Blanco-Ponce, Emilia; Carmona-Carmona, Jesús; Arboleda Sánchez, J. A.; Rodríguez Yáñez, Juan Carlos; Soto Blanco, José Manuel; Fernández García, Isabel; Castillo Caballero, José M.; García-Rubira, Juan C.; Hidalgo-Urbano, Rafael J. (Frontiers in Cardiovascular Medicine, 2022)
Background: The net clinical benefit of ticagrelor over clopidogrel in acute coronary syndrome (ACS) has recently been questioned by observational studies which did not account for time-dependent confounders. We aimed to assess the comparative safety and effectiveness of ticagrelor versus clopidogrel accounting for non-adherence in a real-life setting Methods: This is a prospective, multicenter cohort study of patients with ACS discharged on ticagrelor or clopidogrel between 2015 and 2019. Major exclusions were previous intracranial bleeding, use of prasugrel or oral anticoagulation. Association of P2Y12 inhibitor therapy with 1-year risk of Bleeding Academic Research Consortium type 3 or 5 bleeding; major adverse cardiac events (MACE), a composite endpoint of all-cause death, nonfatal myocardial infarction, non-fatal stroke, or urgent target lesion revascularization; definite/probable stent thrombosis; vascular death and net adverse clinical event (a composite endpoint of major bleeding and MACE) was analyzed according to the “on-treatment” principle, using fully adjusted Cox and Fine-Gray regression models with doubly robust inverse probability of censoring weighted estimators. Results: Among 2070 patients (mean age 63 years, 27% women, 62.5% ST-elevation myocardial infarction), 1035 were discharged on ticagrelor and clopidogrel, respectively. Ticagrelor-treated patients were younger, had less comorbidities, but higher rates of medication noncompliance, compared with clopidogrel users. After comprehensive multivariate adjustments, ticagrelor did not increase the risk of major bleeding compared with clopidogrel (subhazard ratio 1.40; 95% CI, 0.96-2.05), while proved superior in reducing MACE (hazard ratio 0.62; 95% CI, 0.43-0.90), vascular death (subhazard ratio 0.71; 95% CI, 0.52-0.97) and definite/probable stent thrombosis (subhazard ratio 0.54; 95% CI, 0.30-0.79); thereby resulting in a favorable net clinical benefit (hazard ratio 0.78; 95% CI, 0.60-0.98) compared with clopidogrel. Results from sensitivity analyses were consistent with those from primary analysis, whereas those from intention-to-treat analysis went in the opposite direction. Conclusions: Among all-comers with ACS, ticagrelor did not significantly increase the risk of major bleeding, while resulting in a net clinical benefit compared with clopidogrel. Further research is warranted to confirm these findings in high bleeding risk populations.